An ecolinguistic perspective on Assyrian-Iranian migrants' portrayal of emotions toward their linguistic resources. (January 2021) - Farsiu, Sara
Abstract: In this study, I explore the relationship between migrants' linguistic resources, their environment, and their emotions, focusing on two Assyrian-Iranian migrants in Germany. By adopting an ecological approach, I examine how the memories they have created in Iran and Germany impact their emotional attachments to the Persian, Assyrian, and German languages. I argue that their experiences with these languages cause them to ascribe distinct emotional values to each. On the one hand, their strong feelings of belonging to a place (Iran), which correspond to their good memories of speaking Persian in that place, lead them to highly value that language and incorporate it into most aspects of their social lives. On the other hand, the migrants' memories of a language with negative or neutral connotations (in this case, German) correspond with a lower level of reported social interactions in that language. This study shows that the language which these participants use to express their emotional involvement in particular moments of their life invokes specific feelings, and represents their inner world better than their other linguistic resources. Highlights: Sentiments towards languages depend on how an individual's experiences with/in various languages unfold over time. Positive social interactions and environmental factors enhance positive emotions towards the language(s) of that place. Memories in a language with negative connotations decrease migrants' reported social interactions in that language.